PENGARUH KUALITAS PRODUK, DUTA MEREK DAN KEPERCAYAAN MEREK TERHADAP MINAT BELI PADA PRODUK SCARLETT WHITENING DI SURABAYA - Aideleyde Chrisyarinta Sulistioki Van Berren; Arief Widijatmoko (Universitas Dharmawangsa, 2023)
The main problem raised in this study is the effect of product quality, brand ambassador, and brand trust on the intention to buy Scarlett Whitening products (a case study in the people of Surabaya). The background of this research is the increasingly widespread development of the skincare industry in terms of quality improvement and promotion involving brand trust and brand ambassador, so that skincare products are increasingly popular with various groups, apart from other factors that encourage them to do skincare, such as increasing self-confidence through bright and healthy skin. Therefore, this study aims to: 1) determine the effect of product quality on buying interest; 2) determine the effect of brand ambassadors on buying interest; 3) determine the effect of brand trust on buying interest; and 4) determine the effect of product quality, brand ambassadors, and brand trust on the interest in buying products of the people of Surabaya in Scarlett Whitening products. Because it seeks to reveal the effect of the independent variable on the dependent variable, the approach used is a quantitative approach. The sample for this study were university students and the people of Surabaya who had bought and used Scarlett Whitening products as many as 106 respondents. Data was collected through questionnaires, which were then analyzed by T-test (partial), F-test (simultaneous), and R2-test (determination) througt the IBM SPSS v 25 for Windows application. The results of this research indicate that: 1) product quality influences buying interest; brand ambassadors have no effect on buying interest; 3) brand trust has an effect on buying interest; and 4) product quality, brand ambassadors, and brand trust simultaneously has an effect on buying interest of the people of Surabaya in Scarlett Whitening products. The ability of the three independent variables to influence the variable of interest in buying products of the people of Surabaya in Scarlett Whitening products simultaneously is 51.8%, with a details of product quality variable contributed 23.7%, the brand ambassador variable contributed 10.8%, while the product trust variable contributed 17.3%.